Twitter as a Discussion Space: Exploring Students' English Communication Patterns - Putra, Setoaji; Syamdianita, Syamdianita; Aridah, Aridah; Rusmawaty, Desy; Kalukar, Ventje Jany (Borneo Educational Journal (Borju), 2025)
This study investigates how students in the English Department at Mulawarman University use Twitter as an informal platform to improve their English communication skills. Unlike traditional classrooms, Twitter offers a relaxed, real-time environment where students interact in English through tweets, slang, memes, and interactions with classmates. Using a qualitative narrative research approach, data were collected from six students and one instructor through semi-structured interviews. Thematic analysis revealed three main findings: students learn English informally through daily practice and self-motivation; they adapt to a flexible communication style influenced by online slang and global discourse; and they benefit from peer interactions that provide feedback, vocabulary models, and confidence-building. This study concludes that Twitter functions not only as a social media tool but also as a dynamic space for authentic, self-directed, and culturally embedded language learning. Unlike previous studies that focus on the formal integration of social media in education, this research highlights the non-academic motivations driving meaningful engagement with English. While acknowledging limitations such as deliberate sampling and digital access, this study offers new insights into how digital platforms support socio-linguistic language development. The research recommends further investigation into long-term impacts and broader student populations to understand the educational value of informal digital learning environments.